2019
DOI: 10.21203/rs.2.12551/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dementia assessment and diagnostic practices of healthcare workers in rural southwestern Uganda: a cross-sectional qualitative study

Abstract: Background An estimated 50 million people worldwide have Alzheimer’s disease and related dementias (ADRD), and this number is projected to increase with the growth of the aging population, with the largest growth occurring in low and middle-income countries. Diagnostic coverage for dementia is estimated to be only 5-10% in low- and middle-income countries. Timely diagnosis of ADRD could prompt early access to information, medical treatments, and support for caregivers. The aim of this study was to assess ho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…A qualitative study carried out in southwestern Uganda noted that health‐care staff did not have adequate specific mental health training for assessment and diagnosis of dementia. Health‐care workers with some specialized training in mental health were more likely to use neuropsychological tests and brain imaging in the diagnosis of dementia 135 …”
Section: Current Evidencementioning
confidence: 99%
“…A qualitative study carried out in southwestern Uganda noted that health‐care staff did not have adequate specific mental health training for assessment and diagnosis of dementia. Health‐care workers with some specialized training in mental health were more likely to use neuropsychological tests and brain imaging in the diagnosis of dementia 135 …”
Section: Current Evidencementioning
confidence: 99%
“…Whilst the Netherlands are renowned for their advanced dementia care both in the community and in long-term care, there are huge variations between high-income and low-and middle-income countries (LMIC). Kamoga et al [15] explored dementia diagnosis and treatment in Uganda and found that health care workers generally had very little training on recognizing and treating dementia symptoms. Those health care workers who were able to recognize symptoms were more likely also to focus on treating other medical symptoms as opposed to those related to dementia.…”
mentioning
confidence: 99%
“…Most continuing education programs in Nigeria focus on other conditions often neglecting impact of physiotherapy in mental health. Qualitative interviewing of physiotherapists in Ireland (Foley et al, 2020) and other healthcare workers in Uganda (Kamoga et al, 2019) revealed little to no training on dementia in medical school and this causes them to lose confidence when caring for people with dementia and they sometimes ignore the symptoms and focus on other comorbidities of dementia. Although these two countries are in different continents and stages of development (developed and developing country) and have different educational system, it is seen that not much attention is paid to dementia during undergraduate training of healthcare professional including physiotherapists.…”
Section: Discussionmentioning
confidence: 99%
“…In Sub Saharan Africa, there is a dearth of studies on knowledge of dementia among health workers. Two of the articles which were found indicated poor knowledge due to lack of training in pre or post medical education and this made some health workers feel less confident and more uncomfortable whenever they encounter people living with dementia or other cognitive impairments (Cettomai et al, 2011; Kamoga et al, 2019).…”
Section: Introductionmentioning
confidence: 99%